Electricity Tariff Design “Theoretical Concepts Vs Practices”: Review of Tariff Design Approaches in East Africa - Case Studies of Rwanda, Kenya, Uganda and Tanzania. - Mburamatare, Daniel; Gboney, William K.; Hakizimana, Jean De Dieu (International Journal of Energy Economics and Policy, 2022)
This paper presents a comparative analysis between the theoretical concepts of tariffs design methodologies and tariff design practices in developing countries especially in East African countries including Rwanda, Tanzania, Uganda and Kenya. The theoretical concepts impose regulatory principles to be followed by the utilities for a fair and efficient tariff. A well-defined and appropriate tariff structure must balance the financial sustainability of the sector on the one hand and the well-being of various segments of society on the other. Even if utilities in regulated markets, especially in East African Countries are currently supposed to apply dynamic pricing models, their governments are still providing significant subsidies and this can create operational inefficiencies. In addition, inappropriate dynamic pricing models can lead to cross subsidization between customers which violate the equity or non-discrimination principle of a good tariff which discourages use by the overcharged and promotes overconsumption by the subsidized. The work presented in this paper evaluate the performance of different methodologies used by developing countries to set electricity prices against the theoretical concepts of electricity dynamic pricing. It also highlights the opportunities and challenges to be addressed in order to set efficient and appropriate tariffs. The conclusion and policy recommendations are provided.